(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article describes the practices of theater researchers offering programming, that meets recognized educational standards, for youth in carceral settings. The article investigates the pedagogy of theater with young people in the female and male sides of a youth facility in Santa Catarina and examines the conditions that surround the process pf theatre making in such a setting. The power dynamics between residents and employees of the facility imbued the work and interfered in the theatrical practice. The article lays out what options for artistic and pedagogical action existed in the workshop and ultimately explains pedagogical and theatrical practice that resulted.